Використання 3D анімації для створення медитативного контенту та вплив на сприйняття глядачів - Попов, К. В. (ХНУРЕ, 2024)
This article explores how 3D animation is used to create meditative content and its impact on viewers' perception. 3D animation serves as a powerful tool in crafting meditative content, inducing relaxation and mindfulness among audiences. The use of 3D animation allows content creators to immerse viewers in serene environments, fostering a sense of tranquility and calmness. Employing techniques like rigging and shading enhances the visual appeal of meditative content, creating lifelike experiences that resonate with viewers on a deeper lev el. Integrating 3D animation into meditative content production offers an efficient means to evoke emotional responses and engage viewers' senses. Strategically incorporating 3D animation transports viewers to tranquil landscapes, facilitating moments of introspection and relaxation.
Keywords: 3D анімація; медитативний контент